Heterotopic Digital Replantation in Mutilating Hand Injuries: An Algorithmic Approach Based on 53 Cases and Literature Review - Chang, Tommy Nai-Jen; Hsu, Chung-Chen; Dafydd, Hywel; Sachanandani, Neil S.; Chen, Lisa Wen-Yu; Chen, Yi-Chieh; Lin, Yu-Te; Lin, Chih-Hung; Lin, Cheng-Hung (Journal of Reconstructive Microsurgery, 2023)
Background Reconstruction of the mutilated hand is one of the most difficult challenges for hand microsurgeons. When multiple digits are amputated, orthotopic digital replantation of the available remnants may not adequately restore the hand function. In such cases, heterotopic digital replantation may provide a more functional reconstruction.Methods Between 1997 and 2018, 53 patients with mutilating hand injuries were treated with heterotopic digital replantation at our institution. A retrospective chart review was conducted to determine the details of the injury, indications for heterotopic digital replantation, and functional outcomes.Results In total, 173 digits were amputated from 53 patients (one patient suffered from bilateral hand injuries, so totally 54 hands). Sixty-eight digits underwent heterotopic digital replantation, 30 digits had orthotopic digital replantation, and 75 stumps were terminalized. The survival rate of digits treated by heterotopic digital replantation and orthotopic digital replantation was 83.8% (57/68) and 86.7% (26/30), respectively (p = 1). Tripod grip was achieved in 83.3% (45/54) of patients following replantation and optional secondary reconstructive surgeries.Conclusion Heterotopic digital replantation is a practical and reliable method for achieving optimal hand function following mutilating hand injuries. The basic principles are to restore a functional thumb in the first instance, followed by at least two adjacent fingers against which the thumb can oppose. This method is particularly indicated when orthotopic digital replantation of the available amputated parts would yield a suboptimal result.
Keywords: heterotopic digital replantation; spare parts surgery; mutilating hand injury; thumb reconstruction